A performance evaluation of a quorum-based state-machine replication algorithm for computing grids - Busca, J. -M.; Bertier, M.; Belkouch, F.; Sens, P.; Arantes, L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2004: Anais do XVI Symposium on Computer Architecture and High Performance Computing, 2004)
Quorum systems are well-known tools that improve the performance and the availability of distributed systems. In this paper we explore their use as a means to achieve low response time for network services that are replicated and accessed over computing grids. To that end, we propose both a quorum construction and a quorum-based state-machine replication algorithm that tolerates crash failures in a partially synchronous model. We show through the evaluation of a real implementation that although simple, this quorum construction and replication algorithm exhibits a response time 20% lower than that of a regular active replication algorithm in appropriate conditions.